Anti-modernism : Radical Revisions of Collective Identity - Mishkova, Diana, 1958-; Turda, Marius; Trencsenyi, Balázs, 1973- (Book collections on Project MUSE., 2014)
The last volume of the Discourses of Collective Identity in Central and Southeast Europe 1770-1945 series presents 46 texts under the heading of 'antimodernism'. In a dynamic relationship with modernism, from the 1880s to the 1940s, and especially during the interwar period, the antimodernist political discourse in the region offered complex ideological constructions of national identification. These texts rejected the linear vision of progress and instead offered alternative models of temporality, such as the cyclical one as well as various narratives of decline. This shift was closely connected to the rejection of liberal democratic institutionalism, and the preference for organicist models of social existence, emphasizing the role of the elites (and charismatic leaders) shaping the whole body politic. Along these lines, antimodernist authors also formulated alternative visions of symbolic geography: rejecting the symbolic hierarchies that focused on the normativity of Western European models, they stressed the cultural and political autarchy of their own national community, which in some cases was also coupled with the reevaluation of the Orient. At the same time, this antimodernist turn should not be confused with rightwing radicalism - in fact, the dialogue with the modernist tradition was often very subtle and the anthology also contains texts which offered a criticism of 'modern' totalitarianism in an antimodernist key.